Back Cover: Green, infrared‐assisted extraction based on statistical modeling for ultra‐high performance liquid chromatography determination of bioactive isoflavones from Puerariae Lobatae. Issue 6 (11th June 2019) - Li, Hua; He, Jingxia; Yin, Rongli; Mou, Qianqian; Bai, Yuqi; Yang, Bin
Abstract : DOI:10.1002/sscp.201900030 The cover picture shows that the developed method of infrared‐assisted extraction and ultra‐high performance liquid chromatographyseparation combined with response surface methodology and desirability function is a reliable, efficient, and green method for simultaneous analysis and quantitation of multi‐components extracted from plants.